2007
DOI: 10.1242/jeb.02706
|View full text |Cite
|
Sign up to set email alerts
|

Structural complexity of chemical recognition cues affects the perception of group membership in the ants Linephithema humile and Aphaenogaster cockerelli

Abstract: SUMMARY Hydrocarbon profiles on the cuticle of social insects act as multi-component recognition cues used to identify membership in a species, a colony or, within colonies, cues about its reproductive status or task group. To examine the role of structural complexity in ant hydrocarbon recognition cues, we studied the species recognition response of two ant species, Linepithema humile and Aphaenogaster cockerelli, and the recognition of conspecifics by L. humile. The cuticular hydrocarbons of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 42 publications
4
63
0
Order By: Relevance
“…In this study, we found that quantitative differences of worker and queen CHC profiles reflect colony identity, and that a statistically derived subset of compounds may mediate colony discrimination. Worker CHC supplementation studies (Greene and Gordon 2007;Torres et al 2007) suggest that a mixture of CHC of different structural classes, with varying ratios across colonies rather than a few compounds from a single structural class, may be used as nestmate recognition cues in L. humile. Our findings support this view and, in addition, suggest that alkenes and monomethylalkanes may be important in queen discrimination, while dimethyl-and trimethylalkanes and other unidentified long-chain CHC may be important in worker recognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that quantitative differences of worker and queen CHC profiles reflect colony identity, and that a statistically derived subset of compounds may mediate colony discrimination. Worker CHC supplementation studies (Greene and Gordon 2007;Torres et al 2007) suggest that a mixture of CHC of different structural classes, with varying ratios across colonies rather than a few compounds from a single structural class, may be used as nestmate recognition cues in L. humile. Our findings support this view and, in addition, suggest that alkenes and monomethylalkanes may be important in queen discrimination, while dimethyl-and trimethylalkanes and other unidentified long-chain CHC may be important in worker recognition.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with studies showing that aggression levels between colonies, or populations, of social insects are based on similarity of genetically-based CHC profiles (Dronnet et al 2006). In L. humile, intraspecific aggression is based on levels of genetic similarity (Tsutsui et al 2000), and is also guided by worker and queen hydrocarbons (Greene and Gordon 2007;Torres et al 2007;. However, the roles of chemical and genetic factors in regulating behavioral interactions among conspecifics have not been tested simultaneously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental work on cuticular hydrocarbons and nestmate recognition has shown that changes in specific subsets of the overall chemical profile are primarily responsible for distinguishing non-nestmates from nestmates (Greene and Gordon, 2007;Martin et al, 2008a;Martin et al, 2008c;Brandt et al, 2009;Guerrieri et al, 2009;van Wilgenburg et al, 2010). Aggression seems to be triggered by recognizing cuticular profiles as being unfamiliar, and the degree of difference from the colony's template correlates with aggression (Suarez et al, 2002;Ozaki et al, 2005;Guerrieri et al, 2009;Martin et al, 2012;Sturgis and Gordon, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These cuticular lipids, synthesized by the animals themselves (Howard and Blomquist, 2005;, and partly obtained from environmental sources (Obin and Vander Meer, 1988;Woodrow et al, 2000;Buczkowski et al, 2005), are typically mixed throughout the colony by means of liquid food transfer, grooming, and exchange through nest material (Soroker et al, 1995;d'Ettorre et al, 2006;Couvillon et al, 2007;Bos et al, 2011). Direct evidence for the use of hydrocarbons in nestmate recognition has been obtained in several ant and bee species, by testing the level of aggression toward NMs supplemented with synthetic hydrocarbons (Lahav et al, 1999;Dani et al, 2005;Ozaki et al, 2005;Martin et al, 2008b;Guerrieri et al, 2009), or to inert materials treated with either the hydrocarbon profile of fellow workers or synthetic mixtures of hydrocarbons (Wagner et al, 2000;Akino et al, 2004;Greene and Gordon, 2007;Martin et al, 2008b). The use of these manipulative experiments has allowed researchers to provide not only direct evidence about the involvement of cuticular hydrocarbons (CHCs) in nestmate recognition, but also information about which compounds constitute the nestmate recognition signal in specific species.…”
Section: Introductionmentioning
confidence: 99%